Penerapan Metode Aktif Debat dalam Meningkatkan Hasil Belajar Siswa pada Materi Konsep Zat - Solissa, Haer; Senimbar, Senimbar (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2023)
This research was motivated by the lack of Physics teachers in applying learning methods that are in accordance with the characteristics of students and the material to be taught so that it affects the quality of learning and learning outcomes in the classroom. The purpose of this study is to apply the active method of debate in improving student learning outcomes on the concept material of class VII substances of Wailua State Junior High School. The type of research used is Classroom Action Research which consists of four stages, namely action planning, action implementation, observation, and reflection with 28 subjects. Data collection techniques are by making observations and tests. Observation is carried out by an observer to observe teacher and student learning activities and tests are used to determine student learning outcomes after participating in learning activities with the application of active debate methods. The results of data analysis found that the average score of students increased, namely in the initial test obtained an average score of 47.14 with a completion percentage of 35.71%, increased in cycle I to 67.14 with a completion percentage of 67.85% and increased significantly in cycle II to 86.07 with a completeness percentage of 96.42%.